Evaluation of lower urinary tract symptoms in multiple sclerosis patients: Review of the literature and current guidelines - Aharony, Shachar Moshe; Lam, Ornella; Corcos, Jacques (Canadian Urological Association Journal, 2017)
Multiple sclerosis (MS) is a unique neurological disease with a broad spectrum of clinical presentations that are time- and disease course-related. MS plaque location (intracranial and/or spinal) is a key feature in the pathophysiology of disease-related lower urinary tract symptoms (LUTS). The prevalence of these symptoms in MS patients is very high, with nearly 90% of them experiencing some degree of voiding dysfunction and/or incontinence. LUTS rarely present as primary MS manifestations and usually appear 6–8 years after the initial diagnosis. Symptom severity usually correlates with the disability status of patients. Patient assessment comprises clinical and advanced investigations. Each patient should be evaluated uniquely, after taking into account his/her symptoms, disease course and length, comorbidities, physical status, and medications. Basic investigation includes detailed history-taking, physical examination, and post-void residual volume measurement. Advanced evaluation consists of imaging and specific testing, with pivotal importance on urodynamic study.